2018
DOI: 10.1038/s41598-018-31257-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for mitigating thermal losses in solar photovoltaics

Abstract: To improve the performance of solar photovoltaic devices one should mitigate three types of losses: optical, electrical and thermal. However, further reducing the optical and electrical losses in modern photovoltaic devices is becoming increasingly costly. Therefore, there is a rising interest in minimizing the thermal losses. These correspond to the reduction in electrical power output resultant of working at temperatures above 25 °C and the associated accelerated aging. Here, we quantify the impact of all po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…6b shows the theoretical and empirical improvements to the panel operating temperature resulting from improvements to the panel average convective heat transfer coefficient. A simplified energy balance model developed by Vallion et al to investigate the pathways for enhancing solar PV efficiency, with some of the results are shown as solid lines 7 . Data points represent mean temperatures for cases measured in this www.nature.com/scientificreports www.nature.com/scientificreports/ experiment.…”
Section: Theoretical Enhancement Due To Convectionmentioning
confidence: 99%
“…6b shows the theoretical and empirical improvements to the panel operating temperature resulting from improvements to the panel average convective heat transfer coefficient. A simplified energy balance model developed by Vallion et al to investigate the pathways for enhancing solar PV efficiency, with some of the results are shown as solid lines 7 . Data points represent mean temperatures for cases measured in this www.nature.com/scientificreports www.nature.com/scientificreports/ experiment.…”
Section: Theoretical Enhancement Due To Convectionmentioning
confidence: 99%
“…In our approach, we considered that PV cleaning maintenance is selected to avoid energy losses from dirt and dust and PV arrays are not affected by shading losses through trees, houses, or other bodies in proximity to PV modules. To reduce losses by temperature (8-15% in the module [85]), we will install spacers to allow 15-20 mm of space between PV modules to allow air circulation and cooling down the PV plant. Many investigations have proved the yearly average daily solar to increase over the years [86,87].…”
Section: Monthly and Yearly Variation In Energy Produced In Pv Arraysmentioning
confidence: 99%
“…Variations in the temperature of solar cells have been theoretically investigated by solving the heat balance equation (El-Adaw, Shalaby, Abdl El-Ghany, & Attallah, 2015) and through finite element (Lee & Tay, 2012). It is revealed that besides maximum value of the daily incident global solar radiation, as well as optical, physical, and geometrical parameters, another leading factor that determines the tempera- Variations in the temperature of solar cells have been theoretically investigated by solving the heat balance equation Vaillon, Dupré, Cal, and Calaf (2018) present the possible strategies that can be deployed to mitigate thermal losses in PV systems and quantified the approaches. Three strategies are stated to be available: maximizing cooling by conduction/convection with a colder medium and by radiation toward the surroundings; minimizing the thermal load (internal heat source) in the panels; and minimizing thermal sensitivity (temperature coefficient) of the electrical power output.…”
Section: Effect Of Temperature On Pv Systemsmentioning
confidence: 99%